Economic Impacts of Digital Innovation on Value-Enhanced Seafood Products: A Pulau Ketam Case Study - Dian Septiana Sari; Annisa Ilmi Faried; Tuan Zamilah Binti Tuan Husain; Widia Br. Ginting (International Journal of Management, Economic and Accounting, 2025)
Digital innovation has emerged as a central driver of competitiveness in coastal economies, particularly within small island communities that rely heavily on fisheries. This study examines the economic impacts of digital platforms, e-commerce adoption, and technology-enabled value-added processing on the seafood sector in Pulau Ketam. Using mixed-method research combining surveys, market data, and stakeholder interviews conducted in 2024–2025, the findings reveal that digital tools significantly increase market access, product visibility, and income stability for seafood producers. Results indicate that value-enhanced products such as processed shrimp, dried fish, marinated crab, and ready-to-cook fillets achieved an average 22–35% price premium after digital marketing adoption. The study further identifies that digitalization supports supply chain traceability, reduces transaction inefficiencies, and enhances consumer trust. Overall, this research shows that digital innovation plays a critical role in strengthening economic resilience and expanding market opportunities for island-based seafood enterprises.